Analisis Faktor-faktor yang Mempengaruhi Tingkat Kemandirian Keuangan Perguruan Tinggi Badan Layanan Umum - Muhammad Luthfi Nurhadi; Dini Rosdini (GLOBAL SCIENTS PUBLISHER, 2025)
Financial independence of Public Service Agency (BLU) higher education institutions is a condition where BLU higher education institutions no longer depend on the allocation of the State Budget and can optimize their resources to generate income to cover operational and capital expenditures to improve service quality. However, BLU in the education sector, the majority of which are higher education institutions, have a low level of financial independence compared to BLU in other sectors. This study aims to identify factors that influence the level of financial independence of BLU higher education institutions. This study uses secondary data in the form of financial reports of 25 BLU higher education institutions during the 2019-2023 period obtained through the Ministry of Finance's PPID page. The sampling method used is purposive sampling. This study uses quantitative research methods and multiple linear regression analysis methods. The results of the study show that the COVID-19 Pandemic, Organizational Size, and Asset Management have a significant positive effect on the Level of Financial Independence of BLU higher education institutions, while Organizational Age and Cash Optimization do not have a significant effect.